Prevalence of Group B Streptococcus Recto-Vaginal Colonization, Vertical Transmission, and Antibiotic Susceptibility Among Pregnant Women in Ethiopia: A Systematic Review and Meta-Analysis - Bekele, Habtamu; Debella, Adera; Getachew, Tamirat; Balis, Bikila; Tamiru, Dawit; Eyeberu, Addis; Tiruye, Getahun; Kure, Mohammed Abdurke; Habte, Sisay; Eshetu, Bajrond; Regassa, Lemma Demissie; Mesfin, Sinetibeb; et al. (Frontiers in Public Health, 2022)
Abstract Background: Maternal Group B Streptococcus (GBS) recto-vaginal colonization is the most common route for GBS diseases during the perinatal period. A good understanding of maternal GBS colonization, vertical transmission rate, and antibiotic susceptibility profiles is needed to formulate a broad protection mechanism like vaccine preparation. For that reason, this meta-analysis aimed at determining the pooled prevalence of GBS recto-vaginal colonization, vertical transmission rate and its antibiotic susceptibility profiles in Ethiopia. Methods: Both published and unpublished studies were searched from MEDLINE/PubMed, CINAHL (EBSCO), Embase, Web of Sciences databases and Google Scholar. Then, independent selection was carried out by the authors based on the eligibility criteria and data extraction using Microsoft excel. The authors then used STATA version 14.1 software for further cleaning and analysis. Using the random-effect model, the prevalence with a 95% confidence interval and forest plot was used to present the findings. Besides, the studies’ heterogeneity was assessed using Cochrane chi-square (I2) statistics while Egger intercept was used to assess publication bias. Results: This review included nineteen studies. The pooled prevalence of rectovaginal colonization was 15% (95% CI: 11.0, 19.00), while prevalence of vertical transmission was 51% (95% CI: 45, 58) and highest level susceptibility to vancomycin was 99% (95% CI (98, 100). However, the GBS susceptibility to tetracycline was 23% (95% CI: 9, 36). Conclusions: Nearly one out of seven pregnant women in Ethiopia had recto-vaginal colonization of GBS. As result, half of the pregnancy is complicated with vertical transmission of GBS. Vancomycin is a drug of choice for GBS in Ethiopia. Hence, the review highlights policy and programs should address the reduction of GBS and vertical transmission, thereby revising first-line antibiotic treatment of GBS to tackle its complications. Keywords: antibiotic susceptibility, colonization, GBS, pregnant women, recto-vaginal.